SEMcTrA: a multilayer specialized system for COVID-19 remote triage, resource allocation and teleconsultation - Silva, Herlan A.; Souza, Daniel F. L.; Oliveira, Leiva C. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2022: Proceedings of the 28th Brazilian Symposium on Multimedia and the Web, 2022)
The rapid regulation of telemedicine in Brazil during the COVID-19 pandemic occurred after publication of the brazilians Unified Health System (SUS) Ordinance No 467/2020 and Federal Council of Medicine (CFM) Resolution 2.314/2022, which provides defini tions, usages and regulations for telemedicine during the pandemic period. Once social isolation actions have been required in pan demic, teleconsultation and remote triage combined solutions pro vide strategic subsidies for monitoring and treating COVID-19. When aggreded with someone allocation strategies, these solu tions allowing exchange of qualified information, and strategic communication within territory, where the residents and the local assistance services are responsible for directly dealing with the pandemic. In this context, the teleconsultation multilayer expert system for COVID-19 classification, triage and intelligent alloca tion so-called SEMcTrA was developed. Composed of asynchronous (patient-system interaction) and synchronous (medical-patient in teraction) communication modules, which legitimize and effective the medical forwarding, and enable the collect of accurate data of the disease evolution. The SEMcTrA computes the probability coefficient of Covid-19, called PCovid, to diagnostic aid decision. The remote communication with the patient is subsidized by the PCovid value in a teleconsultation environment that implements Security Assurance Level requirements. In addition, the system has a homepage for news publication to serve the population with secure information regards the new coronavirus. The system is currently being tested by the team from Division of Health Care Employee (DASS) at the Universidade Federal Rural do Semi-Árido. As a result, the multilayer triage approach (asynchronous, synchro nous, and smart allocation) encapsulated in the SEMcTrA, provided support for medical-decision by offering information in an efficient and agile way to combat the pandemic.